[PP.09.10] LEFT VENTRICULAR HYPERTROPHY (LVH) IN RENAL DISEASE: IMPACT OF CLASSIC CARDIOVASCULAR RISK FACTORS. (September 2016) - Perez-Monteoliva, N. Robles; Bayo, M.; Candia, B. Gonzales; Fuentes, M.; Fernandez-Berges, D.; Cubero, J.
Abstract : Objective: The contributions of the traditional cardiovascular risk factors and the uremia-specific ones to the development of LVH in the renal patient remains to be elucidated. We have examined the prevalence of LVH in a group of chronic kidney disease (CKD) patients and its relationships with classic cardiovascular risk factors. Design and method: Retrospective study of the patients attending the Nephrology Outpatient Office. The abbreviated MDRD4-IDMS equation for traceable creatinine was used to estimate GFR. Urinary protein and urinary albumin excretion (UAE) were measured in 24 h urine collection. In all 1, 155 patients had at least one two-dimensional guided M-mode echocardiogram examination performed during the follow up. They were males 57.7% (95% CI 54.8–60.5). The prevalence of patients with GFR below 60 ml/min was 38, 7% (n = 455, 95% CI 54.8–60.5), subjects in stage III were 75.6% (95% CI 70.4–80.2) and 24.4% (95% CI 19.9–29.6) were in stage IV. Results: In all the prevalence of LVH was 61.3%. Only 28.6% of patients showed no findings in echocardiogram. Prevalence of LVH among patients with GFR < 60 ml/min was 68.5% vs 56 for those with GFR > 60 (p < 0.001). The prevalence of LVH was increased in patients with microalbuminuria 66.5% and macroalbuminuria 71.3% compared to those with normoalbuminuria 54.4% (p < 0.001). Logistic regression analysis showed that only high blood pressure, dyslipidemia, diabetes mellitus, obesity, and chronic heart failure were independently associated with the presence of LVH in echocardiogram. Contrariwise, CKD was not independently associated with this problem. Conclusions: A high prevalence of LVH among non-dialysis CKD patients was found. Classic cardiovascular risk factors (high blood pressure, dyslipidemia, diabetes mellitus, obesity) and chronic heart failure were independently associated with the presence of LVH in echocardiogram. Contrariwise, CKD was not independently associated with the presence of LVH.